2017
DOI: 10.5380/biofix.v2i2.53539
|View full text |Cite
|
Sign up to set email alerts
|

Panorama Dos Combustíveis E Biocombustíveis No Brasil E as Emissões Gasosas Decorrentes Do Uso Da Gasolina/Etanol

Abstract: RESUMO ABSTRACTA busca por alternativas para reduzir a extração do petróleo e a preocupação com a emissão de poluentes na atmosfera reforçam cada vez mais a importância da produção comercial dos biocombustíveis. Nesse cenário, desde a década de 1970, o etanol é comercializado no Brasil, e desde 2005 existem esforços para o biodiesel alcançar proporções significativas na matriz energética brasileira. A literatura referente às emissões gasosas oriundas da queima de diesel/biodiesel e gasolina/etanol reporta a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
1
0
6
Order By: Relevance
“…The complexity of the ethanol production chain in Brazil is because both the Northeastern and Southern models are typically formed by small and medium production units and are mainly associated with associative production and family agriculture. These types of resources change the profiles and relationships of the production chain, charging a greater understanding of the development of environmental, political, economic, social, ethical, and technological measures appropriate for the respective actions [8]. Concerning competitiveness in biofuels, it is observed that Brazil, in the long term, will pursue technological innovations to meet the demand for expansion of this energy source.…”
Section: Methodology 21 Competitiveness In Biofuelsmentioning
confidence: 99%

Economic and Competitiveness Analysis of Di-Amyl Ether as an Aviation Biofuel

Andressa Germann Avila,
André Brum Missaggia,
Deoclécio Junior Cardoso da Silva
et al. 2023
ARFMTS
“…The complexity of the ethanol production chain in Brazil is because both the Northeastern and Southern models are typically formed by small and medium production units and are mainly associated with associative production and family agriculture. These types of resources change the profiles and relationships of the production chain, charging a greater understanding of the development of environmental, political, economic, social, ethical, and technological measures appropriate for the respective actions [8]. Concerning competitiveness in biofuels, it is observed that Brazil, in the long term, will pursue technological innovations to meet the demand for expansion of this energy source.…”
Section: Methodology 21 Competitiveness In Biofuelsmentioning
confidence: 99%

Economic and Competitiveness Analysis of Di-Amyl Ether as an Aviation Biofuel

Andressa Germann Avila,
André Brum Missaggia,
Deoclécio Junior Cardoso da Silva
et al. 2023
ARFMTS
“…A procura por alternativas energéticas menos poluentes aumenta a importância e a demanda comercial pelos biocombustíveis, com foco notável para a produção de etanol (Ribeiro, Schirmer, 2017). Isto porque, este combustível é importante aliado na busca por menores emissões de gases de efeito estufa (GEE) no setor de transporte, auxiliando diretamente na mitigação das mudanças climáticas causadas pelo uso extensivo dos combustíveis fósseis (Renewable Fuels Association, 2023).…”
Section: Introductionunclassified
“…Diante dos problemas ocasionados pela queima de combustíveis fósseis, eleva-se a necessidade pela busca de alternativas sustentáveis. Assim, pesquisas têm sido realizadas a fim de desenvolver melhores soluções para as demandas energéticas globais (Cardoso; e, entre as alternativas, destacam-se os biocombustíveis (Schirmer & Ribeiro, 2017), com isso, avanços importantes estão ocorrendo nas produções de etanol, biogás, bioquerosene e biodiesel nas últimas décadas (Rezende & Pasa, 2017).…”
Section: Introductionunclassified